2017
DOI: 10.3389/fphys.2017.00138
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Inhibition Limits Angiotensin II-Induced DNA Oxidation and Protein Nitration in Humans

Abstract: Compared to other cyclooxygenase-2 inhibitors, celecoxib is associated with a lower cardiovascular risk, though the mechanism remains unclear. Angiotensin II is an important mediator of oxidative stress in the pathophysiology of vascular disease. Cyclooxygenase-2 may modify the effects of angiotensin II though this has never been studied in humans. The purpose of the study was to test the effects of selective cyclooxygenase-2 inhibition on plasma measures of oxidative stress, the vasoconstrictor endothelin-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…Cyclooxygenases (COX) and nicotinamide adenine dinucleotide phosphate oxidases (NADPH oxidases/NOX) represent the primary group of enzymes involved in the generation of ROS. Overexpression of COX-2 has been associated with angiotensin-II induced oxidative stress signaling pathways and CH [47]. In the present study, co-exposure of the H9C2 cells with YDR and ISP led to an inhibition in the over-expression of COX-2 mRNA triggered by ISP alone.…”
Section: Discussionsupporting
confidence: 57%
“…Cyclooxygenases (COX) and nicotinamide adenine dinucleotide phosphate oxidases (NADPH oxidases/NOX) represent the primary group of enzymes involved in the generation of ROS. Overexpression of COX-2 has been associated with angiotensin-II induced oxidative stress signaling pathways and CH [47]. In the present study, co-exposure of the H9C2 cells with YDR and ISP led to an inhibition in the over-expression of COX-2 mRNA triggered by ISP alone.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, the appearance of nitrated proteins can be regarded as a sign of severe stress by combined actions of RNS and ROS, as they occur when peroxynitrite is protonated or forms CO 2 adducts, followed by cleavage into oxidizing radicals and • NO 2 . This is observed in various different pathologies [ 129 , 130 , 131 , 132 , 133 , 134 , 135 ], such as cardiovascular [ 136 , 137 , 138 , 139 ] and neurodegenerative diseases [ 140 , 141 , 142 , 143 , 144 , 145 ], but also under conditions of ischemia/reperfusion [ 146 , 147 , 148 , 149 , 150 , 151 , 152 ]. In addition, mutagenic and carcinogenic effects occur, when DNA is hit by ROS and RNS, especially peroxynitrite: DNA bases are modified by RNS that cause nitration (e.g., formation of 8-nitroguanine) [ 153 , 154 , 155 , 156 , 157 ], deamination (e.g., xanthine) [ 85 , 158 ] or both (e.g., 8-nitroxanthine) [ 159 ].…”
Section: Pathophysiological Relevance Of Actions Against Nitration Rns-mediated Oxidation and Nitrosylationmentioning
confidence: 99%
“…It has been reported that the brain Ang II is increased in patients with hypertension [50]. Ang II was also found to be involved in the regulation of COX2 function, while COX2 inhibition limits the effects of Ang II in humans [51,52]. Hence, we supposed that the function of COX2 and metabolism of PGE 2 are likely to be disturbed in human hypertension.…”
Section: Discussionmentioning
confidence: 85%